Redesign of Production and Retail Activities at Flower Shop, Inc. in Puerto Rico (LACCEI, 2024)
Abstract – Flower Shop, Inc is a luxury flower shop located in Puerto Rico. In 2020, it experienced a 603% increase in demand, which resulted in moving from a kiosk to a full-size establishment. Several opportunities related to customer service and materials management emerged from this move. Some alternatives to improve the process included a Flower Price Calculator, Future Order Entry System, SIMIO simulation, 5S and others. With the alternatives selected an 85% reduction in scrap and a 9.9% reduction in service time was achieved.